Intraovarian Injection of Autologous Platelet-Rich Plasma Improves Therapeutic Approaches in The Patients with Poor Ovarian Response: A Before-After Study - Nazli Navali; Leila Sadeghi; Laya Farzadi; Aliyeh Ghasemzadeh; Kobra Hamdi; Parvin Hakimi; Behrooz Niknafs (International Journal of Fertility and Sterility, 2022)
Background: Advanced age is associated with a decline in the natural oocytes, low oocyte yield, and also increases the assisted reproductive technology (ART) failure rate, and consequently resulted in a pregnancy rate decrease. Platelet-rich plasma (PRP) is one of the proposed therapeutic strategies for women with poor ovarian response (POR). Because of the autologous source of PRP, the lowest risks of disease transmission, immunogenic and allergic reactions have been expected. This study aimed to evaluate the single-dose intraovarian injection of autologous PRP in poor ovarian reserve.Materials and Methods: We conducted a clinical trial study in the Al-Zahra hospital and Milad Infertility Clinic, Tabriz, Iran (April and May, 2021). A total of thirty-five women with a POR and mean age 40.68 ± 0.34 enrolled in this study. After injection of autologous PRP into the ovaries, the number of oocytes, antral follicles, and level of estradiol, anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH), luteal hormone (LH), FSH/LH ratio also were evaluated while, these parameters were evaluated before PRP administration. Results: At the 2-month follow-up, women treated with PRP showed a significant elevation in the number of oocytes (3.68 ± 0.24, P=0.0043) and embryos (3.17 ± 0.14, P=0.0001), as well as in the estradiol levels (404.1 ± 16.76 vs. 237.7 ± 13.14, P=0.0003). Conclusion: Single PRP injection is effective and might be a promising therapeutic approach in the patients with POR to conceive with their own oocytes, although further evidence is required to assess the influence of PRP on the live birth rate.